Electronic origin of high-temperature superconductivity in single-layer FeSe superconductor - Liu, Defa; Zhang, Wenhao; Mou, Daixiang; He, Junfeng; Ou, Yun-Bo; Wang, Qing-Yan; Li, Zhi; Wang, Lili; Zhao, Lin; He, Shaolong; Peng, Yingying; Liu, Xu; et al. (Nature communications, 2012)
The recent discovery of high-temperature superconductivity in iron-based compounds has attracted much attention. How to further increase the superconducting transition temperature ( T c ) and how to understand the superconductivity mechanism are two prominent issues facing the current study of iron-based superconductors. The latest report of high- T c superconductivity in a single-layer FeSe is therefore both surprising and significant. Here we present investigations of the electronic structure and superconducting gap of the single-layer FeSe superconductor. Its Fermi surface is distinct from other iron-based superconductors, consisting only of electron-like pockets near the zone corner without indication of any Fermi surface around the zone centre. Nearly isotropic superconducting gap is observed in this strictly two-dimensional system. The temperature dependence of the superconducting gap gives a transition temperature T c ~ 55 K. These results have established a clear case that such a simple electronic structure is compatible with high- T c superconductivity in iron-based superconductors. The exact mechanism for superconductivity in iron-based superconductors remains elusive, but is thought to involve complex interactions between many orbitals. Using angle-resolved photoelectron spectroscopy, Liu et al . report the electronic structure of the single-layer parent compound FeSe.